Cannabis Reform, ‘Medical and Scientific Purposes’ and the Vienna Convention on the Law of Treaties - Rick Lines (International Community Law Review, 2018)
This article examines the proposition put forward by several authors that a legally regulated market in cannabis may be permissible under the international drug control treaties if considered as a policy ‘experiment’.